ASSESSMENT OF HAEMATOLOGICAL PARAMETERS OF PUNGANUR CATTLE - A. KAVYA and G. NAGI REDDY, (The Journal of Research ANGRAU, 2023)
The study was undertaken with the objective of establishing the normal reference values of certain haematological parameters in Punganur cattle maintained at Livestock Research Station, Palamaner in Andhra Pradesh. Twenty-four healthy Punganur cattle in different physiological stages (calves, bulls and lactating cows) during the month of August, 2022 were selected for the study. Blood samples were collected from jugular vein during morning hours before feeding. Hematological profile such as total red blood cells (RBC), haemoglobin (HB), total white blood cells (WBC), packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) etc. were estimated with automatic blood analyser. The range of values for haematological parameters such as RBC (6.77 ± 0.60 to 9.59 ± 0.59 million/ìl), WBC (8.20 ± 1.10 to 10.33 ± 1.23 thousands/ìl), haemoglobin content (8.51 ± 0.52 to 10.50 ± 0.49 g/dl), PCV (28.75 ± 2.36 to 32.25 ± 2.05 %), MCV (31.30 ± 0.38 to 42.90 ± 1.42 fl), MCH (8.79 ± 0.12 to 14.07 ± 0.45 pg), MCHC (28.27 ± 0.33 to 33.93± 0.18 g/dl) and the cells in differential leukocyte count (Lymphocytes: 3.88 ± 0.49 to 4.98 ± 0.93 thousands/ìl, Monocytes: 0.75 ± 0.08 to 1.35 ± 0.13 thousands/ìl and Granulocytes: 0.37 ± 0.10 to 0.50 ± 0.10 thousands/ìl) were recorded for different stages. The normal haematological values established in the study could be helpful in the diagnosis of different ailments in Punganur breed of cattle at different physiological stages and the values can also useful for academic purposes.